2004
DOI: 10.4102/sajp.v60i2.185
|View full text |Cite
|
Sign up to set email alerts
|

Self-responsibility predicts the successful outcome of coronary artery bypass surgery

Abstract: Purpose: This study was designed to determine whether the acceptance of self-responsibility is an important determinant of the successful outcome of coronary artery bypass graft (CABG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…1 However due to improvement of surgical techniques, cardiac anesthesia, myocardial protection during bypass and perioperative intensive care the patients with impaired left ventricular function have shown better results after surgical revascularization which helps to recruit the contractile reserve after CABG. 7,8 In our study, mean EF improved from 37.12±5.69% preoperatively to 45.80±10.00% postoperatively after 90 days of follow up which was statistically significant. In patients with impaired LV function due to stunned myocardium or hibernating myocardium, revascularization helps to recruit the myocardial reserve and improve the LV function.…”
Section: Discussionsupporting
confidence: 56%
“…1 However due to improvement of surgical techniques, cardiac anesthesia, myocardial protection during bypass and perioperative intensive care the patients with impaired left ventricular function have shown better results after surgical revascularization which helps to recruit the contractile reserve after CABG. 7,8 In our study, mean EF improved from 37.12±5.69% preoperatively to 45.80±10.00% postoperatively after 90 days of follow up which was statistically significant. In patients with impaired LV function due to stunned myocardium or hibernating myocardium, revascularization helps to recruit the myocardial reserve and improve the LV function.…”
Section: Discussionsupporting
confidence: 56%
“…Some authors correctly note that coronary artery bypass grafting (CABG) carries increased risk in this patient group. Indeed, several authors have suggested that recruitable contractile reserve is an important determi­nant of improvement after CABG in ischemic heart di­sease patients who undergo surgery (primary for heart failure) ( 11 , 12 , 13 ). Patients without such reserve are less likely to benefit simptomatically from CABG whereas those with reser­ve are.…”
Section: Discussionmentioning
confidence: 99%